Review of the spider genus Ectatosticta Simon, 1892 (Araneae: Hypochilidae) with description of four new species from China - Wang, Lu-Yu; Zhao, Jing-Xia; Irfan, Muhammad; Zhang, Zhi-Sheng (Zootaxa, 2021)
Species of the genus Ectatosticta Simon, 1892 are studied from China, including seven known species E. bajie Lin & Li, 2021 from Sichuan Prov., E. davidi (Simon, 1889) from Shaanxi, E. deltshevi Platnick & Jäger, 2009 from Qinghai, E. rulai Lin & Li, 2021 from Sichuan, E. wukong Lin & Li, 2020 from Sichuan, E. xuanzang Lin & Li, 2020 from Tibet, E. yukuni Lin & Li, 2021 from Shaanxi, and four new species: E. nyingchiensis sp. nov. from Tibet, E. pingwuensis sp. nov. from Sichuan, E. shennongjiaensis sp. nov. from Hubei and E. songpanensis sp. nov. from Sichuan. We provide detailed descriptions, including DNA barcode information, and images of all the species.